2D Axisymmetric Model Research of Helical Heat Exchanger inside Pile Foundations. (2017) - Liu, Wenbo; Xu, Minghai
Abstract: A 2D axisymmetric model was established and numerical simulation method was used to study the transient state heat conduction status of helical buried pipe heat exchangers inside pile foundations. The temperature field and heat exchange amount under operating conditions in summer and winter were obtained via simulation. Calculation results indicated that during the initial system operation phase, when the temperature difference between the water inside the helical pipe and the surrounding soil was large, the heat exchange rate was high. As the system operated, the temperature of the soil surrounding the helical pipe increased (or decreased) and the temperature difference between the pipe wall and the soil rapidly decreased, as did the exchange amount per metre of pipe length. The heat exchange amount per unit of pipe length in summer was always greater than that in winter. If area ratios when using air conditioners inside high-rise buildings were large, then pile foundation helical buried pipe heat exchangers could only satisfy a partial air conditioning load.